Pengembangan Modul Sosialisasi Moderasi Beragama untuk Majelis Taklim melalui ADDIE - Ramadhani, Sarah Ayu; Al Hakim, Hisamuddin; Ubaidillah, Annisa; Prasetya, Ganang Ghandi (Universitas Cokroaminoto Yogyakarta, 2026)
The development of religious moderation study materials for majelis taklim is important to enhance participants’ understanding. This development research uses the Analyze, Design, Development, Implementation, Evaluation (ADDIE) model. The results of the needs analysis indicate that the congregation has practiced moderation, but does not yet understand the concept of moderation terminologically. The developed study module contains concepts, indicators, supporting verses and hadiths, and relevant case studies of religious moderation. Validation from religious moderation experts, language experts, and learning technology developers showed an average score of 4.41, thus the module was declared very suitable for use. Effectiveness testing through observation showed an increase in the congregation's understanding of the term religious moderation, this was seen from their active participation in discussions, as well as their ability to identify the application of moderation values ​​in everyday life. This module can be used as a learning guide for religious moderation in Islamic study groups.